Writing by doing learning to write effectively - Hughes, Elaine; Sohn, David A.; Sohn, David A. (Lincolnwood, Ill. National Textbook, 1997)
Provides instruction in personal writing, paragraph writing, longer compositions, and language skills, with activities and exercises for practice and review.
Includes index.
Rev. ed. of: Writing by doing / David A. Sohn, Edward Enger. 2nd ed. c1990.
Keywords: English language -- Composition and exercises; English language -- Composition and exercises; English language -- Grammar; English language -- Grammar